Reviewing Statutory Models of Mediation/Conciliation in New Zealand: Three Conclusions - Baylis, Claire (Victoria University of Wellington Law Review, 1999)
In the last two decades there has been a trend in New Zealand of enacting statutory models of mediation/ conciliation. This article raises concerns about the treatment of fundamental process issues in the many statutory models and the inconsistencies between the models. The article is based on current research by the author which will be completed by the end of 1999. Some funding for this project has been gratefully received from the Victoria University of Wellington Foundation through the New Zealand Institute for Dispute Resolution.